Sporadic vestibular schwannoma: a molecular testing summary. Issue 4 (23rd June 2020) - Sadler, Katherine V; Bowers, Naomi L; Hartley, Claire; Smith, Philip T; Tobi, Simon; Wallace, Andrew J; King, Andrew; Lloyd, Simon K W; Rutherford, Scott; Pathmanaban, Omar N; Hammerbeck-Ward, Charlotte; Freeman, Simon; et al.
Abstract : Objectives: Cases of sporadic vestibular schwannoma (sVS) have a low rate of association with germline pathogenic variants. However, some individuals with sVS can represent undetected cases of neurofibromatosis type 2 (NF2) or schwannomatosis. Earlier identification of patients with these syndromes can facilitate more accurate familial risk prediction and prognosis. Methods: Cases of sVS were ascertained from a local register at the Manchester Centre for Genomic Medicine. Genetic analysis was conducted in NF2 on blood samples for all patients, and tumour DNA samples when available. LZTR1 and SMARCB1 screening was also performed in patient subgroups. Results: Age at genetic testing for vestibular schwannoma (VS) presentation was younger in comparison with previous literature, a bias resulting from updated genetic testing recommendations. Mosaic or constitutional germline NF2 variants were confirmed in 2% of patients. Pathogenic germline variants in LZTR1 were found in 3% of all tested patients, with a higher rate of 5% in patients <30 years. No pathogenic SMARCB1 variants were identified within the cohort. Considering all individuals who received tumour DNA analysis, 69% of patients were found to possess two somatic pathogenic NF2 variants, including those with germline LZTR1 pathogenic variants. Conclusions: Undiagnosed schwannoma predisposition may account for a significant minority of apparently sVS cases, especially at lower presentation ages. Loss of NF2 function is a common event in VS tumours and may represent a targetable common pathway in VS tumourigenesis. These data also support the multi-hit mechanism of LZTR1 -associated VS tumourigenesis.